2021
DOI: 10.1108/cdi-08-2021-0217
|View full text |Cite
|
Sign up to set email alerts
|

Publishing quantitative careers research: challenges and recommendations

Abstract: Purpose This article aims to provide prospective authors guidelines that will hopefully enable them to submit more competitive manuscripts to journals publishing careers research.Design/methodology/approach Based on their experience as an author, reviewer and editorial team member, the authors identify the main criteria that a quantitative study must meet to be considered for publication in international peer-reviewed journals covering career-related topics. They emphasize the importance of contributing to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 78 publications
(80 reference statements)
0
26
0
Order By: Relevance
“…First, a time-lagged study does not allow us to sufficiently conclude the causal association between leader secure-base support and employee job crafting, test why leader secure-base support may influence employee job crafting (i.e. the mediating role of state promotion focus), or examine their reciprocal relationships (Schreurs et al. , 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, a time-lagged study does not allow us to sufficiently conclude the causal association between leader secure-base support and employee job crafting, test why leader secure-base support may influence employee job crafting (i.e. the mediating role of state promotion focus), or examine their reciprocal relationships (Schreurs et al. , 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Future research could also conduct longitudinal studies to explore whether and how leader secure-base support and employee job crafting may influence each other over time as well as build longitudinal mediation models (e.g. cross-Leader securebase support and job crafting lagged panel models, latent growth curve models, latent change score models) to examine why leader secure-base support may relate to employee job crafting (Schreurs et al, 2022). Second, all study variables were reported by employees; thus, common method variance might have biased our results.…”
Section: Limitations and Future Research Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The bibliographic paper in this special anniversary issue (Varma et al, 2022) presents a range of empirical data showcasing the publications in CDI over the last 25 years graphically, while Schreurs et al (2021) paper examines the challenges of publishing quantitative careers research. Here, we offer the qualitative perspective, providing detailed information about the qualitative research published in the journal over this time.…”
Section: Bibliometric and Visual Analyses Of Qualitative Research Pub...mentioning
confidence: 99%
“…Moreover, we did not measure negative emotions and instigated workplace incivility at Time 1 and thus cannot assess change in these variables over time. To further validate our findings, future research needs to use a longitudinal design such as constructing a random intercept cross-lagged panel model (Schreurs et al. , 2022).…”
Section: Discussionmentioning
confidence: 86%